(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines the competencies acquired during the training of primary school teachers, which is quite naturally related to the fact that the main result of the teacher’s activity should be the harmonious, comprehensive and all-encompassing development of the younger generation. Successful acquisition by primary school learners of knowledge and skills within a particular academic discipline is only possible if the teacher himself distinctly and clearly understands what methods, technologies and techniques can be used to improve the quality and efficiency of the educational process.